DIGITAL TECHNOLOGY IMPACTS ON THE LABOUR MARKET AND THE TRANSPORT INDUSTRY - Bibhuti B Pradhan , Priyabrata Pattanaik (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The economy and culture are constantly evolving. Digital transformation is one of the main drivers of the transition. Digital transformation is not only focused on the internet, but above all on the new digital technologies which have become an integral part of life. They not only influence the society and economy but the transportation industry as well. The digitalisation cycle has provided opportunities for new goods, technologies and processes. At the other hand, it has introduced risks of digitalisation or so-called digital disruption. Such risks come in the form of new obstacles for employers and workers, as with any other industrial revolution. Digital technology as well as digital services alter employability laws and workplace competency standards, expertise, skills and attitudes. Start encouraging online job sites, and changing local and global labour markets. On the basis of this fact, the purpose of this paper is to analyse, define and characterize the impact of digital technologies on the labour market and its potential impact on the labour market in transport.